The mediating effect of brand awareness on the influence of social media advertising on consumer purchase decision in the milk tea industry - Matias, Kent Louie C. (Animo Repository, 2022)
Milk Tea has been a well-loved product throughout the past decade. Since it has been popularized and made known to the international market, this has opened up many opportunities for milk tea businesses to open and has allowed existing brands to add more products to their menu. Given their nature as a business, brands have also adapted to the digital age and made use of various social media platforms in hopes of building awareness and increasing influence amongst their target market online. With this, the study explores the current purchase decisions of consumers that are impacted by social media advertisements. As such, this study centers on exploring the influence of social media advertising on consumers' purchase decisions, alongside the mediating effect of brand awareness, within the milk tea industry. The study was conducted through a distribution of online survey questionnaires that were administered to 300 total respondents, which consisted of students and employed individuals. Multiple Regression, Simple Linear Regression, Correlation Matrix, and Mediation analysis were the methods utilized in this study to examine the data. The correlation analysis presented a positive correlation of 0.648 between social media advertising and consumer purchase decisions and displayed a higher correlation of 0.670, between social media advertising and brand awareness. The multiple regression analysis also showcased the high significance between all variables, with a p-value less than 0.001. The linear regression model manifested the same result, garnering a t-value of 16.3. Through a mediation analysis, both the indirect and direct effects are significant with a p-value of less than 0.001, which signifies that brand awareness only partially mediates the effect of social media advertising on consumer purchase decisions. With these in mind, it was concluded that all three of the alternative hypotheses are accepted, which presents the variables to have a significant impact on the purchasing decisions of milk tea consumersMilk Tea has been a well-loved product throughout the past decade. Since it has been popularized and made known to the international market, this has opened up many opportunities for milk tea businesses to open and has allowed existing brands to add more products to their menu. Given their nature as a business, brands have also adapted to the digital age and made use of various social media platforms in hopes of building awareness and increasing influence amongst their target market online. With this, the study explores the current purchase decisions of consumers that are impacted by social media advertisements. As such, this study centers on exploring the influence of social media advertising on consumers' purchase decisions, alongside the mediating effect of brand awareness, within the milk tea industry. The study was conducted through a distribution of online survey questionnaires that were administered to 300 total respondents, which consisted of students and employed individuals. Multiple Regression, Simple Linear Regression, Correlation Matrix, and Mediation analysis were the methods utilized in this study to examine the data. The correlation analysis presented a positive correlation of 0.648 between social media advertising and consumer purchase decisions and displayed a higher correlation of 0.670 between social media advertising and brand awareness. The multiple regression analysis also showcased the high significance between all variables, with a p-value less than 0.001. The linear regression model manifested the same result, garnering a t-value of 16.3. Through a mediation analysis, both the indirect and direct effects are significant, with a p-value of less than 0.001, which signifies that brand awareness only partially mediates the effect of social media advertising on consumer purchase decisions. With these in mind, it was concluded that all three of the alternative hypotheses are accepted, which presents the variables to have a significant impact on the purchasing decisions of milk tea consumers.